2019
DOI: 10.1177/0886260519872982
|View full text |Cite
|
Sign up to set email alerts
|

Cyber Dating Abuse Victimization: Links With Psychosocial Functioning

Abstract: It is well established that technology can be used to enact intimate partner violence (IPV). However, less is known about how cyber dating abuse (CDA) is associated with psychosocial functioning, especially when accounting for other forms of frequently co-occurring IPV victimization. The current study sought to determine the unique associations of CDA victimization when controlling for multiple forms of in-person IPV victimization. Two hundred seventy-eight men and women between 17 and 25 years of age ( M = 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 58 publications
3
28
0
4
Order By: Relevance
“…A high prevalence of DV among this young population illustrates profound mental health implications. Moreover, DV was found to be associated with behavioral abnormalities, alcoholism and substance abuse, and several psychiatric comorbidities (Burton et al, 2016;Duerksen & Woodin, 2019;Y. Park et al, 2018;Taquette & Maia Monteiro, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A high prevalence of DV among this young population illustrates profound mental health implications. Moreover, DV was found to be associated with behavioral abnormalities, alcoholism and substance abuse, and several psychiatric comorbidities (Burton et al, 2016;Duerksen & Woodin, 2019;Y. Park et al, 2018;Taquette & Maia Monteiro, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, DV profoundly impacts the psychosocial processes and mental health of the victims (Temple et al, 2016). Studies have shown high prevalence of psychiatric comorbidities including depression, anxiety, substance abuse, stress disorders, and posttraumatic stress disorder among the victims of DV (Burton, Halpern-Felsher, Rehm, Rankin, & Humphreys, 2016;Duerksen & Woodin, 2019; Y. Park, Mulford, & Blachman-Demner, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Almost every respondent who noted having experienced intimate partner sexual, physical, and emotional violence also documented experiencing intimate partner cyber violence (92.6, 96, and 94.8%, respectively;Marganski and Melander, 2015). Thus, cyber intimate partner violence is perhaps a form of violence on its own and exacerbates and contributes to other forms of in-person intimate partner violence (Duerksen & Woodin, 2021), warranting further exploration.…”
Section: Impact Of Technologymentioning
confidence: 99%
“…To measure perpetration of CDA, participants completed a modified (Supplementary Data) version of the Cyber Aggression in Relationships Scale (CARS). 48 Although originally threefactor approach to the CARS was recommended, 48 more recent research 49 found no satisfactory factor structure or model fit and recommended treating the CARS as unidimensional. The CARS is composed of 16 items [''Sent threatening or harassing messages to my partner via text or social media'' and ''I have checked my partner's messages (e.g., e-mail, Facebook, phone) without them knowing''; a = 0.96].…”
Section: Acceptance Of Modern Myths About Sexual Aggressionmentioning
confidence: 99%